Dosimetry for New Radiation Therapy Approaches Using High Energy Electron Accelerators - Kokurewicz, Karolina; Schüller, Andreas; Brunetti, Enrico; Subiel, Anna; Kranzer, Rafael; Hackel, Thomas; Meier, Markus; Kapsch, Ralf-Peter; Jaroszynski, Dino A. (Frontiers in Physics, 2020)
We have performed dosimetry studies using electron beams with energies up to 50 MeV, which exceed current clinical energy ranges and approaches the bottom end of the very high energy electron range. 50 MeV electron beams can reach deep-seated tumors. In contrast to photon beams, electron beams can be generated with ultra-high dose rates by linear accelerators, which could enable FLASH radiotherapy of deep-seated tumors. The response of radiochromic film and alanine is compared with dose measurements using an ionisation chamber. Energy dependence is not observed within the measurement uncertainty in the investigated energy range from 15 to 50 MeV.